BIOSYNTHESIS, CHARACTERIZATION AND EVALUATION OF SILVER NANOPARTICLES FROM THE LEAF EXTRACT OF PREMNA INTIGRIFOLIA L. AS A POTENTIAL ANTICANCER AGENT - K., SPANDANA; SHETTAR, ARUN K.; S., RASHMI (International Journal of Applied Pharmaceutics, 2024)
Objective: In this study, plant-based silver nanoparticles were synthesized and characterized from Premna integrifolia leaf extract to test the viability towards anticancer properties. Methods: Preliminary identification of silver nanoparticles was validated by Visual observation and confirmed for the characterization by Scanning Electron Microscopy (SEM), Energy Dispersive X-ray Spectroscopy (EDX) and Fourier-transform Infrared Spectroscopy (FTIR) analysis. Further synthesized nanoparticles were evaluated against non-small lung cancer cells (A549) by MTT (3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide) assay. Results: Aqueous leaf extract of Premna intigrifolia was synthesized for silver nanoparticles and showed an average size from 35nm to 100 nm through SEM studies. EDX showed a strong signal confirming the formation of silver nanoparticles in the metallic silver region at 5Kev, and the FTIR spectrum showed changes in some peaks of the aqueous extract with functional groups. The newly synthesized silver nanoparticles showed significant anticancer properties targeting lung cancer A549 cell line against standard drug Epotoside with a 50% Inhibitory Concentration (IC50) value of 78.431 µg. Conclusion: The results affirm that biosynthesized silver nanoparticles can be used as an alternative to chemical medicines to cure cancer.